PERCEPTIONS AND ATTITUDE ON USING SOCIAL MEDIA RESPONSIBLY: TOWARD SOCIAL MEDIA LITERACY IN NURSING EDUCATION - Ryan Michael Flores Oducado; Mhonica Reyes Sales; Aira Joy Piz Magarzo; Patricia Mae Arboleda Panes; Joreem Theus Paniza Lapastora (Belitung Raya Foundation, Indonesia, 2019)
Background: As future professionals, nursing students are expected to exhibit online professionalism and to be responsible users of social media. However, the rapid sharing of information on social media exposes nursing students to the risk and danger of spreading unprofessional behaviors like breaches of privacy and confidentiality. Objective: This study looked into the nursing students’ perceptions and attitude toward responsible use of social media. Methods: A descriptive cross-sectional research design was utilized and participated by 298 nursing students in a College of Nursing in Iloilo City, Philippines. The Responsible Use of Social Media Attitude Scale (RUSMAS) created by the researchers was used to collect the data. Results: Findings indicated that nursing students widely use social media and that nursing students had good perceptions and had positive attitude toward responsible use of social media. A significant difference was found in the attitude of nursing students when grouped according to year level. Conclusion: Social media continue to gain interest among nursing students and using it responsibly must be continuously upheld. Academic nursing institutions should develop approaches promoting social media literacy in nursing education.